COMPARISON OF ANTIBACTERIAL CHITOSAN OF HARUAN FISH SCALES (Channa striata) WITH Chlorhexidine gluconate AGAINST Lactobacillus acidophilus - Tomy Wira Wahyuda; Deby Kania Tri Putri; Muhammad Yanuar Ichrom Nahzi (Universitas Lambung Mangkurat, 2023)
Background: Lactobacillus acidophilus plays an important role in the development of caries, especially advanced caries. Mouthwash such as chlorhexidine is the main choice to prevent the colonization of caries-causing bacteria, but in long-term use it causes side effects, so that new, more biocompatible materials are needed, namely chitosan of Haruan fish scales (Channa striata), which contains an amine group (Nh2). Purpose: To analyze and compare the antibacterial effectiveness of chitosan haruan fish scales at concentrations of 2.5%, 5%, 7.5%, and 10% with chlorhexidine gluconate 0.2% on the growth of Lactobacillus acidophilus bacteria. Method: True Experimental Laboratory Research with a procedure consisting of making chitosan from Haruan fish scales through the processes of deproteination, demineralization, and deacetylization followed by an antibacterial test with 5 treatment groups on the growth of Lactobacillus acidophilus bacteria using the diffusion method with inhibition zone parameters on the test material. Result: Haruan fish scale chitosan has the lowest antibacterial effectiveness, namely a concentration of 2.5% with an average inhibition zone value of 8.6 mm, and the highest is a 10% concentration with an inhibition zone average value of 21.3 mm, and a concentration of Haruan fish scale chitosan. 10% had antibacterial effectiveness comparable to 0.2% chlorhexidine gluconate against the growth of Lactobacillus acidophilus bacteria. Conclusion: Haruan fish scale chitosan concentrations of 2.5%, 5%, 7.5%, and 10% had antibacterial effectiveness against the growth of Lactobacillus acidophilus bacteria, and a concentration of 10% was comparable to 0.2% chlorhexidine gluconate in inhibiting the growth of Lactobacillus acidophilus bacteria. Keywords : Caries, chitosan haruan fish scales, Lactobacillus acidophilus.